2021
DOI: 10.3390/s21113650
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Prediction of the Recovery of Carotid Blood Flow during Cardiopulmonary Resuscitation in a Swine Model

Abstract: The recovery of cerebral circulation during cardiopulmonary resuscitation (CPR) is important to improve the neurologic outcomes of cardiac arrest patients. To evaluate the feasibility of an electroencephalogram (EEG)-based prediction model as a CPR feedback indicator of high- or low-CBF carotid blood flow (CBF), the frontal EEG and hemodynamic data including CBF were measured during animal experiments with a ventricular fibrillation (VF) swine model. The most significant 10 EEG parameters in the time, frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As for animal models [7,[32][33][34][35][36], ventricular fibrillation was medically induced and treated following a standard protocol. In all these cases, EEG showed a good correlation with cerebral blood flow recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for animal models [7,[32][33][34][35][36], ventricular fibrillation was medically induced and treated following a standard protocol. In all these cases, EEG showed a good correlation with cerebral blood flow recovery.…”
Section: Resultsmentioning
confidence: 99%
“…While results in animal models are promising [7,[32][33][34][35][36], literature data in humans are still controversial. Few studies suggested that BIS ™ or PSi values, and/or EEG analysis might reflect cerebral oxygenation [11,[17][18][19][20][21][22][23]; nevertheless, others showed that BIS ™ values, and EEG monitoring are not reliable indicator of cerebral function due to mechanical artifacts related to external chest compression and involuntary head movements [26].…”
Section: Discussionmentioning
confidence: 99%
“…First, we were unable to stratify the types of CPR interventions due to the heterogeneity of CPR interventions (including defibrillation, anti-arrhythmic drugs, adrenergic drugs, and mechanical CPR). Efforts were made to provide specific information in each article in Supplementary Material B [40–256] to identify the type of VF induction used in the experiment of interest. Second, the quality of the included studies was not assessed.…”
Section: Discussionmentioning
confidence: 99%